Media Pembelajaran Final Line Assembly Contactor Tesys D Size 1&2 Berbasis Video - Henny Juliana (Politeknik Negeri Batam, 2020)
Learning video is a learning process where users watch and listen and then get information in the form of knowledge and skills. Previously the operator was collected in class and got paper containing only pictures and writings, now operators can do learning on the laptop that has been provided by having a lot of material in the form of videos. The learning video is also equipped with an explanation dubbing, images of what material will be taken by the operator until the assembly process is finished or the product finished good. The method in this study uses the EPIC Model to measure the effectiveness of the video which has 4 dimensions, namely the Empathy Dimension, the Persuasion Dimension, the Impact Dimension and the Communication Dimension. The results of the video will be uploaded on the digital training website that is already available.